ANALISIS PENGARUH KOMPETENSI KARYAWAN DAN DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN KARYAWAN HOTEL XYZ DEPOK - Tridayana Sitanggang; Edison Siregar; Poerwaningsih S. Legowo (Fundamental Management Journal, 2026)
The main objective of this research is to identify the extent to which employee competence and work discipline affect service quality at Hotel XYZ Depok. In the hospitality industry, service quality is a strategic aspect that heavily depends on the role of human resources. This study employs a quantitative approach with an associative design to analyze the relationships among variables. The research involved 128 hotel customers selected based on their direct experience in receiving services, using a questionnaire measured with a 5-point Likert scale. The instrument testing results indicate that all items are valid and reliable, as shown by Cronbach’s Alpha values exceeding 0.6 for all variables. Furthermore, multiple linear regression analysis was applied with the assistance of IBM SPSS Statistics version 30 to obtain hypothesis testing results.Employee competency showed a significant positive influence on employee service quality (β = 1.213; t = 7.555; p < 0.001). Work discipline also had a significant positive influence (β = 0.578; t = 5.669; p < 0.001). Simultaneously, both variables significantly influenced employee service quality (F = 203.157; p < 0.001) with a coefficient of determination R² = 0.765, explaining 76.5% of the variance in employee service quality. The contribution of this research provides understanding for hotel management to improve service quality through employee competency development and work discipline strengthening as an effective operational strategy. Keywords: employee competency, work discipline, employee service quality, hospitality industry